The supply-side of international corruption: a new measure and a critique - Picci, Lucio (European journal on criminal policy and research, 2018)
I consider the supply-side of corruption in the context of international bribery, which I define as firms bribing public officials abroad. I present the Bribe Payers Corruption Index (BPCI), a non-perception-based measure of cross-border corruption coherent with a simple analytical framework based on an important distinction: that between the propensities to corrupt and observed levels of corruption. The BPCI is compared with a widely known indicator of the supply-side of corruption, Transparency International’s Bribe Payers Index (TI-BPI), which I demonstrate to be flawed. Whereas according to the TI-BPI firms from corrupt countries are more likely to bribe abroad, the opposite emerges when the BPCI is considered. I explain and discuss such results, the implications of which are framed within the global discourse on the supply-side of international corruption.